Transmission of Bamboo mosaic virus in Bamboos Mediated by Insects in the Order Diptera - Chang, Kuo-Chen; Chang, Ling-Teng; Huang, Ying-Wen; Lai, Yi-Chin; Lee, Chin-Wei; Liao, Jia-Teh; Lin, Na-Sheng; Hsu, Yau-Heiu; Hu, Chung-Chi (Frontiers in Microbiology, 2017)
Bamboo mosaic virus (BaMV), a member of the genus Potexvirus, is the major threat to bamboo cultivation. Similar to most potexviruses, the transmission of BaMV by insect vectors has not been documented previously. However, field observations of BaMV disease incidences suggested that insect vectors might be involved. In this study, we aimed to investigate the possibility of insect-mediated transmission of BaMV among bamboo clumps, in order to provide further insights into the infection cycles of BaMV for the development of effective disease management measures. From the major insects collected from infected bamboo plantations, BaMV genomic RNAs were detected inside the bodies of two dipteran insects, Gastrozona fasciventris and Atherigona orientalis, but not in thrips (Scirtothrips dorsalis). Artificial feeding assays using green fluorescent protein (GFP)-tagged BaMV virions revealed that BaMV could enter the digestive systems and survive in the regurgitant and excretion of the dipterans. BaMV RNA could be retained in the dipterans for up to 4 weeks. Insect-mediated transmission assays indicated that both dipterans could transmit BaMV to bamboo seedlings through artificially created wounds with low infection efficiency (14 – 41 %), suggesting that the dipterans may mediate the transmission in a mechanical-like manner. These results demonstrated that dipterans with sponge-like mouthparts may also serve as vectors for at least one potexvirus, BaMV, among bamboo plants. The finding suggested that dipteran insect control should be integrated into the disease management measures against BaMV infections.